Implementation of Dialogical Sequence Analysis as a Case Formulation for the Assessment of Patients at a Community Mental Health Centre: Randomized Controlled Pilot Study - Savander, Enikő Éva; Pänkäläinen, Mikko; Leiman, Mikael; Hintikka, Jukka (European Journal of Mental Health, 2019)
Background: We implemented a case formulation method, which is based on dialogical sequence analysis (DSA) in a community mental health center. The aim was to achieve better congruence and collaboration between the patient and professionals concerning the tasks and goals of the assessments. Here we report a randomized clinical study in which we compare DSA-based and standard psychiatric assessments.Methods: In this randomised clinical study, we compared DSA‑based and standard psychiatric assessments. There were 40 outpatients in both, the DSA and the assessment as usual (AAU) groups. We recorded the lengths of individual assessment periods, the number and durations of visits, and the numbers of clinicians who were involved in the various phases of assessment. The Working Alliance Inventory was completed by the patients (WAI-P) and the clinicians (WAI-T) during the treatment planning (i.e. final) visit.Results: In our results, the total WAI-P and WAI-T scores and all WAI subscale scores correlated significantly in the DSA group (Spearman’s rho = 0.562–.667, p < 0.01). In the AAU group, the only significant – albeit weaker – correlation was found in the WAI Bond subscale (rho = 0.369, p < 0.05). Compared to the AAU group, assessment periods were shorter and the number of visits were fewer in the DSA group.Conclusion: Our findings are clinically notable. They show that the patient-centred, DSA-based case formulation complements psychiatric assessment in a collaborative way and results in a better joint understanding regarding the patient’s problems and needs in a shorter time period than the standard assessment.